Islamic Political Communication in Winning the Hearts of Millennial Voters - Dharta, Firdaus Yuni; Lee, Ava; Tan, Ethan (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
In the rapidly evolving political landscape, the influence of millennial voters is becoming increasingly significant, especially in predominantly Muslim countries where political communication plays a crucial role in shaping public opinion. Islamic political communication, which blends traditional religious values with modern political strategies, is an important tool in engaging millennial voters. This study examines the effectiveness of Islamic political communication in winning the hearts and minds of millennial voters in Indonesia, where the millennial demographic is a critical force in the political sphere. The study uses a qualitative research approach, conducting interviews with political communicators, social media influencers, and millennial voters, along with content analysis of political campaigns targeting this demographic. The findings indicate that Islamic political communication that is authentic, relatable, and values-driven resonates most with millennial voters. Moreover, the use of digital platforms, such as social media, is found to significantly enhance engagement and build trust with younger voters. The research concludes that Islamic political communication can be an effective strategy in gaining the support of millennial voters by aligning political messages with Islamic principles and youth-centered concerns. Future studies should further explore the impact of digital media on political communication and voter behavior among millennial Muslims.